2022
DOI: 10.1021/acs.energyfuels.2c01256
|View full text |Cite
|
Sign up to set email alerts
|

Defect Engineering in Graphitic Carbon Nitride Nanotextures for Energy Efficient Solar Fuels Production: A Review

Abstract: Excessive release of greenhouse gas carbon dioxide (CO2) into the atmosphere and continuous utilization of fossil fuels has resulted in global warming and energy shortage. Among the different alternatives, photocatalytic conversion of CO2 to fuels and hydrogen production is a promising approach. To achieve this goal, highly efficient and low-cost semiconductor are demanding to maximize solar energy conversion to renewable fuels. In this perspective, metal free two-dimensional (2D) graphitic carbon nitride (g-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 164 publications
0
30
0
Order By: Relevance
“…[15,16] Artificial photosynthesis in particular has attracted considerable research interest over the past few decades, since it offers the possibility of producing chemical products that traditionally rely on fossil fuels using waste CO 2 . [15,17] Various technologies have been implemented in artificial photosynthesis process, such as biocatalysis, [18,19] thermocatalysis, [20,21] photocatalysis, [22][23][24][25][26] electrocatalysis, [27][28][29] as well as photoelectrocatalysis. [30] Electrochemical CO 2 reduction (ECO 2 R) has attracted considerable attention due to its unique advantages, which include the relatively mild operating conditions; the tunable product selectivity and reaction path by regulating reaction Excessive anthropogenic CO 2 emission has caused a series of ecological and environmental issues, which threatens mankind's sustainable development.…”
mentioning
confidence: 99%
“…[15,16] Artificial photosynthesis in particular has attracted considerable research interest over the past few decades, since it offers the possibility of producing chemical products that traditionally rely on fossil fuels using waste CO 2 . [15,17] Various technologies have been implemented in artificial photosynthesis process, such as biocatalysis, [18,19] thermocatalysis, [20,21] photocatalysis, [22][23][24][25][26] electrocatalysis, [27][28][29] as well as photoelectrocatalysis. [30] Electrochemical CO 2 reduction (ECO 2 R) has attracted considerable attention due to its unique advantages, which include the relatively mild operating conditions; the tunable product selectivity and reaction path by regulating reaction Excessive anthropogenic CO 2 emission has caused a series of ecological and environmental issues, which threatens mankind's sustainable development.…”
mentioning
confidence: 99%
“…24,77–80 There are various reviews discussing in detail the preparation methods of g-C 3 N 4 . 21,28,81–83…”
Section: Graphitic Carbon Nitride Propertiesmentioning
confidence: 99%
“…105 Doping is a type of point defect where impurities or foreign atoms are introduced, which disrupts the original lattice structure of the material. 193 A study conducted by Syzgantseva et al reported that the doping of metals into the lattice of MOFs is able to modulate the energy band gap of MOFs. Here, two MOFs, namely, MIL-125-NH 2 and UiO-66-NH 2 , were doped with different types of metals, and their E bg were observed.…”
Section: Active Sites Over Ti 3 C 2 Tmentioning
confidence: 99%